MEPs elicited by multidirectional rotational-field TMS show marked differences compared to unidirectional Figure-of-8 and H7 coils - Orit Wonderman Bar Sela; Shay Ofir Geva; Gaby S. Pell; Yiftach Roth; Jason Friedman; Afnan Muhana; Silvi Frenkel-Toledo; Nachum Soroker (PLoS ONE, 2026)
Unidirectional transcranial magnetic stimulation (udTMS; e.g., via Figure-of-8 coil) depolarizes mainly neurons whose axonal orientation aligns with the direction of the induced electric field. A novel dual H-coil (T360°) TMS system (BrainsWayTM, Israel) generates a rotational magnetic field aimed to recruit a larger neuronal population by induction of a multidirectional electric field (rfTMS). This study aimed to comparatively assess the neurophysiological properties of motor evoked potentials (MEPs) elicited from the first dorsal interosseous (FDI) muscle following udTMS (via Figure-of-8 and H7 coils) vs. multidirectional rfTMS. In this study, 10 healthy adult subjects received TMS via the three coil configurations in a random order. The results showed that rfTMS elicited larger MEPs at a lower resting motor threshold (rMT) compared to the unidirectional coils. These findings suggest that rfTMS is likely to recruit larger populations of neurons compared to conventional udTMS coil configurations. This may be advantageous in efforts to enhance motor recovery following brain damage by treatments using TMS.